PEMANFAATAN MEDIA GAMBAR BERSERI UNTUK MENINGKATKAN KETERAMPILAN MENULIS TEKS DESKRIPSI SISWA KELAS III SEKOLAH DASAR - Arifin, Septiani Nuraini; Kironoratri, Lintang; Santoso, Denni Agung (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2025)
This study aims to improve the descriptive writing skills of third-grade students using the Think Talk Write learning model with the aid of a series of picture media. The research uses the Classroom Action Research (CAR) method, which is conducted in two cycles, with each cycle consisting of two meetings. The subjects of this study are 26 third-grade students from SDN 2 Undaan Lor. Data collection techniques include observation, interviews, tests, and documentation, with expert judgment validation, consisting of media and material experts. The data obtained are analyzed qualitatively and quantitatively. The results of the study show that in the pre-cycle, the average classical score for descriptive writing skills was 63, categorized as good. In Cycle I, the average classical score for descriptive writing skills increased by 10.2%, with a score of 69.432, categorized as good. In Cycle II, the classical score for descriptive writing skills increased by 20.5%, reaching a score of 80.192, which was categorized as excellent. Thus, it can be concluded that the Think Talk Write learning model can improve the descriptive writing skills of third-grade elementary school students.